Analisis Prinsip-Prinsip Desain Pada Karya Ternama Bauhaus - Noah James (VisArt: Jurnal Seni Rupa dan Design, 2024)
In the world of visual communication design, the name "Bauhaus" certainly sounds familiar. Apart from being known as an experimental and contemporary result that started the development of modernist design, the Bauhaus had a huge effect on the development of design in the period 1919-1933. His approach to education and the relationship between art, society, and technology had a profound influence on Europe and America long after those countries closed under Nazi pressure. Until the Bauhaus design form has been proven to be a type of design that has survived for a long time. The main problem is to see evidence of various forms of design such as architecture, furniture and interiors today which are the result of the design effect. The main objective is to analyze the design elements of famous Bauhaus works, such as Marcel Breuer's Cesca Chair which was created in 1928. Researchers used qualitative research methods in the form of observation to determine the quality of design works from that period which were proven to survive over time. which is old. The results of this research study show that there was the influence of the thinking of that era or the zeitgeist which formed a main principle in the design of the Bauhaus period, one of which was "form follows function". These rules have had a significant impact on design from that period to the present. Overall, the three Bauhaus principles succeeded in creating a unique, functional, and aesthetic design style. Bauhaus works are not only historical relics, but are still valuable today and provide inspiration for many contemporary designers.